Pengaruh Komunikasi Pramuwisata Lokal Terhadap Kunjungan Wisatawan di Daya Tarik Wisata Budaya Pura Luhur Uluwatu Desa Pecatu Bali - Anak Agung Ngurah Yoga Widyanatha; Made Darmiati; Dewa Gede Ngurah Byomantara (J-TRUE: Journal of Travel and Leisure, 2024)
This study aims to determine The Effect Of Local Tour Guide Communications On Tourist Visit To The Luhur Uluwatu Temple, Pecatu Village, Bali, Indonesia. This research was conducted using a purposive sampling technique on 100 respondents who use the services of local tour guides at the cultural tourist attraction of Luhur Uluwatu Temple. The data collection technique was carried out using a questionnaire and had tested its validity and reliability. Based on the test results, the coefficient value is 0.076 (positive) with a significant level of 0.003 <0.05, so that HO is rejected and Ha is accepted. This proves that the Communication of Local Tour Guides has a significant positive effect partially on Tourist Visits at the Cultural Tourism Attraction of Luhur Uluwatu Temple, Pecatu Village, Bali.